Life stories of caregivers looking after a child with autism in Vietnam - Dung Thi Nguyen (Politeknik Negeri Bali, 2020)
This study aimed to explore how autistic children form the lives of people who were raising them through life stories shared by caregivers. The research participants included 11 Vietnamese caregivers who were taking care of children diagnosed with autism. A preliminary interview prior to the study was conducted to determine caregivers who would participate in the research and in-depth interviews were carried out with volunteer caregivers. To determine aspects of life stories that shape caregivers’ lives, the study implemented the